Vacuum Cherenkov radiation and bremsstrahlung from disformal couplings - van de Bruck, Carsten; Burrage, Clare; Morrice, Jack (IOPScience, 2016)
The simplest way to modify gravity is to extend the gravitational sector to include an additional scalar degree of freedom. The most general metric that can be built in such a theory includes disformal terms, so that standard model fields move on a metric which is the sum of the space time metric and a tensor constructed from first derivatives of the scalar. In such a theory gravitational waves and photons can propagate at different speeds, and these can in turn be different from the maximum speed limit for matter particles. In this work we show that disformal couplings can cause charged particles to emit Cherenkov radiation and bremsstrahlung apparently in vacuum, depending on the background evolution of the scalar field. We discuss the implications of this for observations of cosmic rays, and the constraints that arise for models of dark energy with disformal couplings.